Communicative perspectives on strategic organization - Vaara, E; Langley, A (SAGE Publications, 2021)
While in the past, perspectives that focus on language and communication have perhaps not received the attention they deserve in the mainstream literature in strategy and organization, interest in this area has been growing in recent years. The present essay serves to introduce a collection of insightful papers (independently submitted and reviewed, but brought together in this themed issue) that offer an opportunity to reflect on the contributions of a rich variety of research perspectives on communication to research in strategic organization. Building on the seven contributions featured in this issue, we show how communicative perspectives speak to questions of the who, how, what, and what then, of strategy. We then discuss dualisms that underpin research on strategic organization adopting a communicative lens and propose directions for future work that might bridge these divides.